Capturing Value amidst Constant Global Restructuring? Information-Technology-Enabled Services in India, the Philippines and Kenya - Jana M. Kleibert; Laura Mann (The European Journal of Development Research, 2020)
Information-technology-enabled services (ITES) has become a sector of promise for many low- and middle-income economies seeking to leapfrog industrialization and build knowledge-intensive economies.~Yet as a sector defined by accelerating processes of commodification and skill elimination, its long-term developmental promise must be carefully scrutinised.~Analysing the development of the sector in India, the Philippines and Kenya the paper~reveals both the contextual nature of past successful ITES policies and their developmental vulnerabilities. Drawing on literature on industrial policies and global value chains and production networks, the paper critiques~the existing policy approaches~by arguing that they are largely focussed on enabling value and employment creation~and that they pay insufficient attention to questions of value capture and long-term socio-economic transformation.
Keywords: 300; Services; Information-Technology-Enabled Services (ITES); Business Process Outsourcing (BPO); Kenya; India; the Philippines